PENGARUH TEKNIK KONTRAK PERILAKU TERHADAP PERILAKU MEMBOLOS SISWA DI SMP NEGERI 5 KOTA JAMBI - Nadia Cantika; Akmal Sutja; Muhammad Zulfikar (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Truancy behavior is a student's behavior that is absent intentionally or because of an invitation from a friend at school without a clear explanation, and leaving certain class hours without the knowledge of the teacher or school. At this time, in fact, some students have high truancy behavior. The purpose of this study is to reduce truancy behavior with a behavioral contract. This study uses an experimental design of one group pre-test post-test control design, which was conducted at SMP Negeri 5 Kota Jambi. Based on the results of the average pre-test score (initial test) of 137 with a percentage of 66.82% in the high category, while the average post-test score (final test) of 85.42 with a percentage of 41.67% is in the moderate category. And the results of the T-test calculation using SPSS 26.0 obtained Tcount of 7.270 with a Sig. (2-Tailed) value of 0.000. Based on the decision-making criteria, there was a significant decrease in truancy behavior before and after treatment was given.